Dialogues between audience research and production: The history of testing television drama for the Danish Broadcasting Corporation. (December 2017) - Redvall, Eva Novrup
This article offers a historical analysis of the audience testing of television drama from The Danish Broadcasting Corporation (DR) by the in-house DR Media Research Department from the mid-1990s until 2016. The article investigates how the methods for testing have changed from more traditional focus groups and surveys to include biometric methods (e.g. skin conductance) to measure audience arousal. While audience testing is often primarily viewed as a quality measurement tool for executives, the article argues that testing can also be a dialogue-based tool offering creative practitioners the opportunity to learn more about their series and their audiences.